Current status of education and research on public health nutrition in Japan: comparison with South Korea, Taiwan, and mainland China - Shinozaki, Nana (BMC Nutr, 2019)
BACKGROUND: Although the importance of capacity building for public health nutrition (PHN) has been increasing globally, reports on the current status of training programs for PHN in East-Asia including Japan are limited. The aim of this study was to compare the current status of education and research activities in the field of PHN in Japan with those in South Korea, Taiwan, and mainland China. METHODS: Necessary information was collected by internet search and telephone inquiry. Collection focused on the number of departments in colleges and universities with PHN as a compulsory subject in the 2016 academic year, and the number of articles and information related to these articles published in the journal Public Health Nutrition between 2007 and 2016. RESULTS: The number of departments with PHN as a compulsory subject was the highest in Japan (n = 137), followed by mainland China (n = 32), Taiwan (n = 18) and South Korea (n = 7). Using the classification list of education in each country and region, the majority of these departments were classified as home economics, natural science, health and welfare, and medical science in Japan, South Korea, Taiwan, and mainland China, respectively. Regarding publications, most of the articles were written in colleges and universities not having PHN as a compulsory subject in Japan, South Korea, and Taiwan. The number of articles per department among departments with compulsory PHN education was lowest in Japan (n = 0.3) compared to Taiwan, mainland China, and South Korea (n = 1.2, 2.7, and 3.7, respectively). CONCLUSIONS: Japan has a much higher number of departments with PHN as a compulsory subject than neighboring East Asian states and relatively low research activities in the field of PHN. This suggests that current university education may not lead to active PHN research in Japan. Further studies are warranted to explore the reasons for this.